Kajian Nilai Pendidikan Karakter Tokoh Kumbakarna Dalam Meningkatkan Mutu Nasionalisme - I Wayan Kantun Mandara; Dika Kamis Wara; I Ketut Angga Irawan; Untung Suhardi; Putu Ersa Rahayu Dewi (Jurnal Penjaminan Mutu, 2020)
The spirit of nationalism should appear in every citizen, including the Alengka Kumbakarna in defense of his country. But, the figure Kumbakarna often neglected for example real in trade off his country. It is forgotten because Kumbakarna giant is to be measured by its evil and do not care. Research that of the value of a character nationalism Kumbakarna and implementation of nationalism in the life of globalization. Methods used in this research was qualitative dekriptif a literature study. Research findings this is the character education kumbarna figure there are seven character is in kumbakarna honest figures, hard work, are, responsibility, social care, love of water, and nationalism. The implementation in the life of , that Kumbakarna have provided it is like giant, but the works that are done that is really have adopted in defense of his country. The real conducted in such a way that all citizens have to have spirit and without forgetting in building his country in a the same thing, using the national language, honor that the symbols the state and proud of the work of the people. All of the family, it is started area environment, the nation in general.